Interação solo-estrutura em galpões metálicos treliçados com cobertura em arco metálico circular - Ferro, Fernando Luiz de Bragança (2013)
The structural design engineer normally considers the soil element that supports foundation of a building behaves as a undeformable solid remains unchanged after application of the load over time. The practice in the design of foundations but indicates that the soil when subjected to loading of a building, it deforms and causes a disturbance in the structure. This phenomenon is called soil-structure interaction and had their computed for metal shed arch truss metallic circular effects. Changes in stresses and strains in the joints of the metal structure and displacements recorded on their joints were studied. The normal stress on the footing-soil interface and displacements occurred were also the object of the study. The procedure compared the solution using immovable supports with hypothesis admitting footing of various sizes by computing the effects of Soil-Structure Interaction. To obtain the results was performed a numerical modeling using finite element method using SAP 2000® software. The results confirmed that the initial estimate was that, even with small dimensions footings supporting large loads resulting from eccentricity moments and still involved only compressive stresses on the soil-footing interface.